Testing the Effect of Job Placement and Career Development on Employees Performance - Nashrudin Setiawan (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
The municipal education office of Medan has an educational motto for all residents of Medan City who have equal rights to get the education, and all educators for the community have a role to educate by their abilities. The problem in this research is whether job placement and career development have a positive and significant effect on the performance of Medan municipality education officials simultaneously and partially. The purpose of this study is to examine the effect of simultaneous and partial of job placement and career development on employee performance. Test results show that F-count has a value of 40.330 and a significant probability of 0.00 < 0.05; the conclusion is career development and job placement have the significant effect on employees performance simultaneously. Therefore, the first hypothesis is confirmed and acceptable. Partial test results show the t-value of 5,729 of the job placement > value t-table 1.672, and significance 0.000 < 0.05. These results proved job placements partially have a positive and significant impact on employees performance. The conclusion is that the proposed hypothesis is confirmed and accepted. Furthermore, the test results partially show the value t-count 5,499 of career development > value t-table 1.672, and significance 0.000 < 0.05. The results of this test proved partially career development have a positive and significant impact on employees performance. Therefore, the researcher's proposed hypothesis is accepted. The results of data processing also show Adjusted R square is worth 0.571 and shows 57.1% contribution of career development variables and job placement on employees performance. Meanwhile, other factors contribute 42.9% worth such as motivation, incentives, and training which are not discussed in this study.